(3QSGdI aj eSCdI JYdjb Ydeg GdbOje HGdCKQ GdMGOKs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde HGdbde hHYO aEfc PcQJ Cfc hGba ai eSCdI JYdb Ydeg JYGdi GdbOje HGdCKQ GdMGOK hbaI MGFQ ebje dchf GdeOGQc GdYbdjI ajg ZGeVI s
(3BNQgG (B:s
(3Ef GdcdGe dai GdaDGO hEfeG LYd GddSGf Ydi GdaDGO OdjdkG hGdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi dhdG Cf gOGfG Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds